Polish Revolt (1863 - 1864) in publications of I.S. Aksakov - Khegay, Victor K. (2019)
In the article, the analysis of judgments of a revolt is provided in the Polish Kingdom and Western edge of one of the main ideologists of Slavophilism of I.S. Aksakov. The key moments of its paradigm on this problem are analyzed, the attempt to discover the reasons for the transformation of views of the Slavophile of the Polish events is made. It is revealed that the aggressive methods of fight practiced by rebels caused resistant hostility in Aksakov and other Slavophiles.